Penggunaan Media Pembelajaran Interaktif dalam Meningkatkan Hasil Belajar Peserta Didik di SDI Khalifah - Rokmanah, Siti; Andriana, Encep; Hakim, Muhamad Lazuardi (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2025)
Educators can utilize the development of sophisticated technology to convey learning more easily so that’s why interactive learning media is very appropriate because they support better student activities and improve student learning outcomes. This research aims to find out that the use of interactive learning media at SDI Khalifah also learning obstacle for the students when using interactive learning media. The method used was a qualitative descriptive method with triangulation techniques for testing the validity of interview data using observation techniques and literature studies. Next, the data was analyzed by using the stages of data reduction, data presentation, and conclusion. The results obtained were interactive learning media used by educators were in the form of interesting animated learning videos and practice questions using the application Kahoot And quiziz which can improve student learning outcomes to be above average or KKM, students who can easily understand the material being studied, and students who are enthusiastic about competing in working on questions to get the highest points.